An offence against the sixth commandment of the Decalogue Canon 1395 §2 and CCEO c. 1453 §1 - Woestman, William H. 1929- (2006)
"The Congregation for the Doctrine of the Faith has given a diocesan bishop permission to conduct an administrative penal process of one of his priests for alleged offenses against the sixth commandment with a minor less than eighteen years of age. In the case at hand the priest was accused of telling dirty stories to a group of adolescent boys. Is this a delict as set forth in c. 1395, §2?"
Keywords: Katholische Kirche; Dekalog; Strafrecht; Ehebruch; Sexueller Missbrauch